Proceedings of the 40th International Symposium on Multiparticle Dynamics 2011
DOI: 10.5689/ua-proc-2010-09/17
|View full text |Cite
|
Sign up to set email alerts
|

Fluctuating initial conditions in hydrodynamics for two-particle correlations

Abstract: Event-by-event hydrodynamics, with fluctuating initial conditions, has shown to nicely reproduce several features of experimentally observed quantities in high-energy nuclear collisions. Here we discuss how it may help to understand, in a unified way, the various structures observed in the long-range two-particle correlations, both in nucleus-nucleus and p − p collisions. Suggestions of how experimentally this description could be tested are also discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2011
2011
2013
2013

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 24 publications
0
14
0
Order By: Relevance
“…More specifically, the data show the existence of structures in the two-particle correlations plotted as function of the pseudorapidity difference ∆η and the angular spacing ∆φ. In [5,6] it has been argued that these structures may have a common hydrodynamic origin: the combined effect of longitudinal high energy density tubes (leftover from initial particle collisions) and transverse expansion.…”
Section: Introductionmentioning
confidence: 99%
“…More specifically, the data show the existence of structures in the two-particle correlations plotted as function of the pseudorapidity difference ∆η and the angular spacing ∆φ. In [5,6] it has been argued that these structures may have a common hydrodynamic origin: the combined effect of longitudinal high energy density tubes (leftover from initial particle collisions) and transverse expansion.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 3 (right) shows that this is indeed the case. We have checked that this structure is robust by studying the effect of several parameters of the model [23]. 6 assoc.…”
Section: Mechanism Ofridge Formation -One-tube Modelmentioning
confidence: 96%
“…In [22], the events computed by using the hydrodynamic code SPheRIO [5], starting from event-by-event fluctuating IC, generated by NeXus [6], were analyzed in a similar way to the experimental ones, in particular the ZYAM method was used to remove effects of elliptic flow. We later developed a different method to remove elliptic flow from our data and checked that all structures are indeed exhibited and other features well reproduced (dependence on the trigger-or associated-particle transverse momentum, centrality, in-plane/out-of-plane trigger, etc) [23,24,25,26].…”
Section: Two-particle Correlations In Hydrodynamic Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…Hydrodynamical studies [1,2] indicate that some experimental features observed at RHIC and LHC can be understood if it is assumed that these tubes survive the thermalization stage and form "tubular" structures that persist for some time during the hydrodynamical expansion in the thermalized quark-gluon plasma (QGP). In [1,2] it has been argued that these structures may have a common hydrodynamic origin: the combined effect of longitudinal high energy density tubes (leftover from initial particle collisions) and transverse expansion. Such tubular structures, which are nearly uniform in the longitudinal direction, may be considered as cylindrical perturbations in the energy density upon a continuous background as depicted in Fig.…”
Section: Introductionmentioning
confidence: 99%